Efficacy of Tranexamic Acid in Reducing Blood Loss during and After Caesarean Section: A Case control Study - Sinha, Kavita; Pandey, Subhash; Khadka, Dipendra (Journal of Nepalgunj Medical College, 2020)
Introduction: The incidence of caesarean section is increasing day by day. One of the most common complications is primary or secondary postpartum haemorrhage. Tranexamic acid has been shown to be very useful in reducing blood loss and incidence of blood transfusion in varieties of surgery. Aims: To study the efficacy of tranexamic acid in reducing blood loss during and after the lower segment caesarean section. Methods: Arandomized, case controlled, prospective study was conducted on 100 women undergoing lower segment caesarean section carried out in the Department of Obstetrics and Gynaecology, Nepalgunj Medical College, Kohalpur from Sept 2019 to Feb 2020.Fifty of them were given tranexamic acid immediately before lower segment caesarean section and were compared with 50 others to whom tranexamic acid was not given. Blood loss was collected and measured during two different time interval. The first period was considered from placental delivery to end of lower segment caesarean section and second from the end of lower segment caesarean section to 2 hours postpartum period. Vital signs at time of delivery, at 1 hour and 2 hour postpartum and APGAR score at 1 min and 5 min were studied in both the groups. Results: Tranexamic acid significantly reduced the quantity of blood loss from the placental delivery to 2 hours post-partum: 360.9 ml in the study group, versus 443 ml in the control group (p=0.0008).It also significantly reduced the quantity of blood loss from the end of lower segment caesarean section to 2 hours postpartum:71.5 ml in the study group versus 112.6 ml in the control group (p=0.0002).There was 18% less incidence of postpartum haemorrhage , who received tranexamic acid(p=0.02).There were no significant adverse drug reaction and difference in APGAR score in both the groups. No complications or side effects were reported in either group. Conclusion: Tranexamic acid is safe and effective in reducing blood loss among women undergoing lower segment caesarean section.